Three-dimensional morphometric analysis of dental arches of children with cleft lip and palate: longitudinal study - Mello, Bianca Zeponi Fernandes de (2018)
This study aimed to present two papers that show the alterations in the dental arch dimensions of children with cleft lip and palate before and after the primary surgeries. The first study aimed to evaluate the dimensional alterations of the dental arches of neonates with unilateral complete cleft lip and palate before and after two different primary plastic surgeries. The sample was composed of 114 dental casts of 57 children, divided into two groups: Group 1 26 neonates whose lip closure was accomplished at 3 months of life by Millard´s technique and the anterior and posterior palate closure by von Langenbacks technique (VL); Group 2 31 neonates whose lip closure, noses ala correction, and anterior palate closure were accomplished of life by Millard´s technique, Mcombs or Skoogs technique, and vomers flap, respectively at 3 months of life; posterior palate closure was accomplished by VL at 12 months of life. The dental casts were analyzed at two phases: (T1) pre-cheiloplasty and (T2) one year after palatoplasty. The second study aimed to evaluate morphometrically and longitudinally the alterations of the dental arch dimensions of children with cleft lip and palate. The sample was composed by digital dental casts of children with complete cleft lip (Group 1), complete cleft lip and palate (Group 2), and complete cleft palate (Group 3), obtained at pre-cheiloplasty (T1), pre-palatoplasty (T2), and one year after palatoplasty (T3). The measurements of the dental arch dimensions of both studies were performed directly on the digitized models and analyzed by Appliance Designer software. The following dimensions were obtained: intercanine distance, inter-tuberosity distance, anterior arch length, and total arch length. A previously trained and calibrated examiner performed the assessments of both studies. To verify the alterations among groups, t test and ANOVA followed by Tukey was applied. In the first study, no statistically significant differences occurred at pre-cheiloplasty. At one year after palatoplasty, Group 1 had statistically significant greater anterior-posterior arch length (P=0.002) than Group 2. This suggested that the outcomes of the different surgical techniques may cause alterations in the dental arch growth and development of neonates with cleft lip and palate. In the second study, in Group 1, the distances C-C, T-T, and I-TT were statistically greater at T2 than at T1. In Group 2, the distances C-C and I-CC were smaller at T3. T-T distance decreased and I-TT distance increased at all phases. In Group 3, the C-C, T-T, and I-TT distances were statistically greater at T3. The intergroup comparisons showed that C-C and T-T distances were statistically greater in Group 1; C-C and I-CC distances were statistically smaller in Group 2; and I-TT distance was statistically greater in Group 3. The longitudinal evaluation of the changes occurred in the dental arches of children with different oral cleft types showed that cheiloplasty and palatoplasty caused the most alterations in the growth and development of the maxillary dimensions of children with complete cleft lip and palate.